Taḥlīl Nuṣūṣ Kitāb al-Lughah al-`Arabiyyah Li aṣ-Ṣaff aṡ-Ṡānī fi al-Marḥalah al-Mutawassiṭah (Dirāsah Taḥlīl al-Muḥtawā Min Ḥaiṡ al-Qawā`id an-Naḥwiyah) - Nisaul Fadhilatinur; Syarifuddin Syarifuddin (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
The book "Darsu Al-Lughah Al-Arabiyah" is one of the books used by students to learn Arabic. This book contains various teaching materials, including the Qawaid Nahwu and reading. After making observations, researchers see that the grammar content in the reading is not in accordance with the grammar material that has been taught. Therefore, this research was conducted to identify the content of reading texts and elements that contradicted grammar material as well as to know the efforts made by the teacher to overcome this problem. This research is content analysis and data collection is done through observation, documentation, and interviews. The sample is the class II book "Darsu Al-Lughah Al-Arabiyah". The results of the study indicate that the content of the reading text in this book consists of grammar that has been learned and grammar that is not learned. Grammar has been studied totaling 77 examples, while those not studied are 144 examples The efforts made by the teacher to overcome this problem are by conducting textbook assessments, observing the material in the book, providing references to other teaching materials, providing additional material, and equip themselves with a variety of knowledge and experience and so on.